2017
DOI: 10.1039/c7bm00554g
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of polysaccharide hemostatic materials and their hemostatic mechanism

Abstract: The formation of stable blood clots or hemostasis is essential to prevent major blood loss and death from excessive bleeding. However, the body's own coagulation process is not able to accomplish timely hemostasis without the assistance of hemostatic agents. For developing novel topical hemostatic agents, tissue adhesives and sealants, it is necessary to understand the coagulation process and the hemostasis mechanism of different materials. Among hemostatic materials, polysaccharides are naturally derived poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
142
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(157 citation statements)
references
References 111 publications
2
142
0
Order By: Relevance
“…[ 42 ] In addition, UPy components had hydrophobic property, and increased UPy components might improve the protein adsorption of hydrogel surface in the blood, accelerating blood clotting. [ 43 ] The results demonstrated that the PEGSD2/GTU5.0 and PEGSD2/GTU7.5 could accelerate the blood clotting.…”
Section: Resultsmentioning
confidence: 99%
“…[ 42 ] In addition, UPy components had hydrophobic property, and increased UPy components might improve the protein adsorption of hydrogel surface in the blood, accelerating blood clotting. [ 43 ] The results demonstrated that the PEGSD2/GTU5.0 and PEGSD2/GTU7.5 could accelerate the blood clotting.…”
Section: Resultsmentioning
confidence: 99%
“…New hemostatic microparticles based on different hemostatic mechanisms had attracted researchers’ enthusiasm. Inspired by the excellent performance of MPH, with the aim of multifunctionalization, more and more multifunctional HMs had been developed . As a bio‐copolymer comprising glucosamine and N ‐acetylglucosamine, chitosan was the alkaline deacetylated product of chitin, and had properties of nontoxicity, biocompatible moisture retention, and being inexpensive .…”
Section: Discussionmentioning
confidence: 99%
“…To mimic platelets, several peptides and antibodies that bind to vWF, collagen, αIIbβ3, and fibrin have been conjugated onto liposomes and polymeric particles 14–17. However, there are still challenging limitations in platelet‐mimicking particles, including complicated conjugation processes and easy clearance by immune systems 18–21. To overcome these limitations, we recently proposed the fabrication of platelet‐derived nanosized vesicles (VEs) as a novel hemostatic biomaterial 22.…”
mentioning
confidence: 90%